2016
DOI: 10.1080/13510002.2016.1240287
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity of (+)-catechin visible-light photoirradiated in the presence of vitamin B2

Abstract: pH-effect of the medium on radical-scavenging activity comes from the increased electron-donating ability of CTQ upon deprotonation. These results are very interesting due to the fact that the pH of the food products displays important variations. The [Formula: see text]-scavenging ability of CTQ, would be equal to the additive contribution of each reactive center, CTC, and RSC, present at the molecule of CTQ. However, CTQ would have a moderate ability to removal of [Formula: see text]-species at pH 7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…Criado, Gutierrez, Avila, Bertolotti, and Garcia (1996b) demonstrated that the ionization of the -OH groups in hydroxyflavones has a great influence on their reaction kinetics. Similar results have been reported for (+)-catechin and derivatives (Barua, Escalada, Bregliani, Pajares, & Criado, 2016).…”
Section: Quantification Of the Interaction Phdsupporting
confidence: 90%
See 1 more Smart Citation
“…Criado, Gutierrez, Avila, Bertolotti, and Garcia (1996b) demonstrated that the ionization of the -OH groups in hydroxyflavones has a great influence on their reaction kinetics. Similar results have been reported for (+)-catechin and derivatives (Barua, Escalada, Bregliani, Pajares, & Criado, 2016).…”
Section: Quantification Of the Interaction Phdsupporting
confidence: 90%
“…As can be seen from both Tables, the ionization of the phenolic group produces a significant increase of k r values. This dependence of k r values on the degree of ionization of -OH group has been reported (Barua, Escalada, Bregliani, Pajares, & Criado, 2016;Bertolotti, Arguello, & García, 1991;García, 1994;). As mentioned above, taking into account the pKa values for Phd, at pH 11-12 a significant percentage of molecules would have their phenolic group ionized.…”
Section: Quantification Of the Interaction Phdsupporting
confidence: 72%
“…flavins + normalhsans-serifν 1flavins 3flavins* where 1 flavins * and 3 flavins * are the excited singlet and triplet states of the flavins, respectively. The degradation mechanisms of these photoinduced flavins were likely initiated by a triplet−triplet annihilation or a triplet–ground state quenching process [25,31,32,33], the latter of which is depicted in this study. The TC directly oxidized by an electron abstraction through an electron transfer event from the TC ground state was started via flovin-sensitised irradiation [25].…”
Section: Discussionmentioning
confidence: 99%